Remoção de óleo do meio filtrante no processo de retrolavagem em filtros de areia - Kirlene Salgado Fernandes (2009)
In the recent years iron and steel making industries have been investing on recycled water treatment aiming at reducing the consumption of water collected in rivers. The motivation for the procedure is the preservation of Brazilian water resources. At present only 4% of the water used in production is collected from hydrographic basins. The major use of water in iron and steel making activities occurs in cooling systems. The aretwo types of cooling systems: in the first water does not contact other materials, keeping its physical and chemical properties. In this case corrosion inhibitors are used in the recirculation water treatment. In the second, water is used to cool a material that is under processing, being then contaminated by iron scale formed on the steel plate surface and by oil from equipments. In this case, prior to corrosion inhibitors application it is necessary to use coagulants and flocculants, in addition to the filtration stage. Filtration is the most important stage, for it will remove the small solid particles in suspension after the decantation of the larger ones. The sand filters, after one filtration cycle must be washed to remove the excess of solid particles retained during the filtration process. Backwashing is used in this case. Since the oil used in the rollingprocess contaminates the recirculation water, it is also retained in filtration, but the backwashing is not capable of removing the oil adhered to the filtration medium. Laboratory experiments were performed aiming at removing the oil from the filtration medium surface with application on backwashing of sand filters in the industrial plant. Laboratory analyses indicated that lubrication oil is the most abundant in contaminatedwater. The most efficient production for its removal, in laboratory experiments, is based on inhibited acids and surfactants. The industrial plant trials with the use of the cleaning agent that yielded the best laboratory result presented satisfactory results, similar to those obtained in the laboratory.